International Conference on Islamic Economics and Economies of the OIC Countries 2009 (American Journal of Islam and Society, 2009)
Amidst the current global interest in searching for possible solutions to thecurrent financial difficulties, the International Conference on IslamicEconomics and Economies of the OIC Countries 2009 (ICIE2009) held inKuala Lumpur, Malaysia, was indeed timely. Held during 28-29 April2009, it provided a platform to promote an intellectual discourse designedto evaluate the current state of the discipline’s various subdisciplines asregards its practical applications. The Department of Economics of theInternational Islamic UniversityMalaysia (IIUM) and the Islamic Researchand Training Institute of the Islamic Development Bank (IDB), adopting aproactive approach, brought together scholars and industry players fromacross the world to analyze how to enhance the theoretical and appliedaspects of Islamic economics, banking, and economic cooperation amongMuslim countries. This event also marked an important date: the IIUM iscelebrating its twenty-fifth-year anniversary, while the OIC is celebratingits fortieth ...